American crows as carriers of vancomycin-resistant enterococci with vanA gene - Oravcova, Veronika; Zurek, Ludek; Townsend, Andrea; Clark, Anne B; Ellis, Julie C; Cizek, Alois; Literak, Ivan (Environmental microbiology, 2014)
We studied the vanA-carrying vancomycin-resistant enterococci (VRE) isolated from American crows in the United States during the winter 2011/2012. Faecal samples from crows were cultured selectively for VRE and characterized. Pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) were used to examine epidemiological relationships of vanA-containing VRE. Isolates were tested in vitro for their ability to horizontally transfer the vancomycin resistance trait. VRE with the vanA gene were found in 15 (2.5%) of 590 crows samples, from which we obtained 22 different isolates. Enterococcal species were Enterococcus faecium (14) and E. faecalis (8). One, two and 19 isolates originated from Kansas, New York State and Massachusetts, respectively. Based on MLST analysis, E. faecium isolates were grouped as ST18 (6 isolates), ST555 (2), and novel types ST749 (1), ST750 (3), ST751 (1), ST752 (1). Enterococcus faecalis isolates belonged to ST6 (1), ST16 (3) and ST179 (4). All isolates were able to transfer the vancomycin resistance trait via filter mating with very high transfer range. Clinically important enterococci with the vanA gene occur in faeces of wild American crows throughout the United States. These migrating birds may contribute to the dissemination of VRE in environment over large distances. [Correction added after first online publication on 06 August 2013: The number of E. faecium ST752 isolate is now amended to '1', consistent with that shown in the 'Results' section and Figure 2.].
Keywords: vrány; Feces; Enterococcus faecium; Carbon-Oxygen Ligases; United States; přenos genů horizontální; ligasy tvořící vazby C-O; rezistence na vankomycin; Bacterial Proteins; Multilocus Sequence Typing; Gene Transfer, Horizontal; zvířata; feces; Vancomycin Resistance; Spojené státy americké; Crows; Enterococcus faecalis; multilokusová sekvenční typizace; bakteriální proteiny; Animals